THE DISSEMINATION OF CHEMISTRY IN SCIENCE MUSEUMS - Palmieri, Luciane Jatoba [UNESP]; Silveira, Camila (Fundacao Univ Tocantins, 2020)
The current article, by means of a literature reviewing, has the objective of presenting and discussing some reflections about how chemistry is disseminated at national and international science museums. We'll be presenting the dissemination of chemistry by three categories: dissemination by means experimentation; dissemination by means daily life; and, dissemination by means of interdisciplinary. The reflections point out to the necessity of overcoming difficulties related to the communication of this science, as well as, the importance of the narrowing between school-museum. We highlight new directives to the initial and processual education of teachers that affirms to the necessity of theorical and practical discussions about non-school environments.
Keywords: Dissemination of Chemistry; Teacher Training; Science Museums